Treatment of seawater salinity sewage with intermittent sand bioreactors - Kristen M. Conroy (IWA Publishing, 2021)
In water stressed areas, flush toilets using fresh water are unsustainable. This paper explores the ability of intermittent sand bioreactors (ISBs) to treat seawater salinity septic tank effluent for on-site wastewater treatment in coastal regions. Two ISB designs, sand only and layered sand and gravel, are compared for treatment efficacy. Six columns of each design were constructed in the laboratory and dosed four times per day, for a total hydraulic loading rate of 4 cm/day, with artificial seawater salinity septic tank effluent over 21 months. Average TOC and ammonia removal for both designs averaged >90% and >96%, respectively. No statistically significant difference existed in the percent removal or effluent concentrations between the two designs. Half of the columns of each design produced effluent with >4 mg/L ammonia at least once during the study, resulting in discontinuation of wastewater application for seven weeks. This resting approach resulted in effective treatment for up to 9 months (limited by the end of the study). The results indicate that both ISB designs can treat artificial seawater salinity septic tank effluent, but that an additional 1/3 capacity is needed to maintain a consistent hydraulic loading rate while accounting for resting ISBs when treatment efficacy declines. HIGHLIGHTS Intermittent sand bioreactors (ISBs) effectively treated seawater salinity septic tank effluent.; One- and three-layer ISBs performed similarly treating seawater salinity septic tank effluent.; Effluent ammonia-N exceeded 4 mg/L at least once in 50% of columns of each ISB design.; Seven weeks of resting restored ammonia removal capacity of ISBs.; Recommend designing systems with 1/3 additional hydraulic loading rate capacity.;